Characteristics and genetic analysis of patients suspected with early-onset systemic lupus erythematosus - Wan-Fang Lee; Wen-Lang Fan; Min-Hua Tseng; Huang-Yu Yang; Jing-Long Huang; Chao-Yi Wu (BMC, 2022)
Abstract Background Systemic lupus erythematosus (SLE) is rarely diagnosed before 5-years-old. Those with disease onset at a very young age are predicted by a higher genetic risk and a more severe phenotype. We performed whole-exome sequencing to survey the genetic etiologies and clinical manifestations in patients fulfilling 2012 SLICC SLE classification criteria before the age of 5. Case presentation Among the 184 childhood-onset SLE patients regularly followed in a tertiary medical center in Taiwan, 7 cases (3.8%) of which onset ≦ 5 years of age were identified for characteristic review and genetic analysis. Compared to those onset at elder age, cases onset before the age of 5 are more likely to suffer from proliferative glomerulonephritis, renal thrombotic microangiopathy, neuropsychiatric disorder and failure to thrive. Causative genetic etiologies were identified in 3. In addition to the abundance of autoantibodies, patient with homozygous TREX1 (c.292_293 ins A) mutation presented with chilblain-like skin lesions, peripheral spasticity, endocrinopathy and experienced multiple invasive infections. Patient with SLC7A7 (c.625 + 1 G > A) mutation suffered from profound glomerulonephritis with full-house glomerular deposits as well as hyperammonemia, metabolic acidosis and episodic conscious disturbance. Two other cases harbored variants in lupus associating genes C1s, C2, DNASE1 and DNASE1L3 and another with CFHR4. Despite fulfilling the classification criteria for lupus, many of the patients required treatments beyond conventional therapy. Conclusions Genetic etiologies and lupus mimickers were found among a substantial proportion of patients suspected with early-onset SLE. Detail clinical evaluation and genetic testing are important for tailored care and personalized treatment.